Design of cold-formed stainless steel circular hollow section columns using direct strength method. (15th May 2018) - Huang, Yuner; Young, Ben
Highlights: Numerical model of stainless steel circular hollow section columns were developed. Finite element analysis of 108 cold-formed stainless steel columns was carried out. Direct strength method (DSM) was assessed by comparing with 273 columns. Modifications are suggested to the direct strength method. Design rule is proposed for stainless steel circular hollow section columns. Abstract: Cold-formed stainless steel circular hollow section (CHS) columns have been increasingly used in construction, due to its aesthetic appearance, long life-span and good ductility. It is shown that direct strength method (DSM) is capable of predicting cold-formed steel column strengths accurately. However, the DSM is developed for cold-formed steel sections with plate rather than curved elements, and thus its applicability for cold-formed stainless steel CHS is worth investigating. This paper presents a numerical investigation of cold-formed stainless steel CHS columns. A non-linear finite element model was developed and verified against column tests. Extensive parametric study of cold-formed duplex, lean duplex and ferritic stainless steel CHS columns has been performed to obtain column strengths. A total of 273 experimental and numerical cold-formed stainless steel CHS column strengths, which are obtained from previous researches and parametric study obtained from this study, are compared with the design strengths predicted by the current DSM. Reliability analysis was performed to evaluate the reliability of the design rules. It is shown that the current DSM provides unconservative and not reliable prediction for cold-formed stainless steel CHS columns. Therefore, modified DSM is proposed for cold-formed stainless steel CHS columns. It is shown that the modified design rule is more accurate than the current DSM, and the modified design rule is considered to be reliable.